Technologická etapa hrubé vrchní stavby bytového domu v Pohořelicích - Hanzl, Martin (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Předmětem bakalářské práce je zpracování technologických etap provádění zděných a stropních konstrukcí vrchní hrubé stavby bytového domu v Pohořelicích. Jedná se o novostavbu čtyřpodlažního objektu označeného B3, jednoho z 10 bytových domů bytového komplexu REZIDENCE MALÝ VINOHRAD v západní části obce Pohořelice. Obsahem bakalářské práce je technická zpráva řešeného objektu se zaměřením na technologickou etapu hrubé vrchní stavby, vypracování technologických předpisů provádění zděných a stropních konstrukcí, časový plán a kontrolní a zkušební plány. Dále je vypracován návrh strojní sestavy, včetně výběru zvedacího zařízení, technická zpráva zařízení staveniště s výkresovou částí a položkový rozpočet s výkazem výměr. Součástí technické zprávy je také řešení bezpečnosti a ochrany zdraví při práci a řešení tepelných mostů balkónových konstrukcí.

The aim of this bachelor‘s thesis is to process the technological stages of the execution of masonry and floor structures of the rough superstructure of a residential building in Pohořelice. It’s a newly-built four-storey building labelled B3 and it’s one of the ten residential buildings in the complex Rezidence Malý Vinohrad, located in the western part of Pohořelice town. This thesis includes a technical report of the building that focuses on the technological stage of the rough superstructure, drawing up of the construction methods used for the execution of masonry and floor structures, the time schedule and the quality control and test plans. The thesis also contains the design of construction machinery including the selection of the lifting machinery and the technical report of the building site equipment. The report includes technical drawings and item budget with a bill of quantities. It also deals with the occupational safety and health regulations and thermal bridges of the balcony constructions.
Technological stage of the rough superstructure of a residential building in Pohořelice
Keywords: Bytový dům; hrubá vrchní stavba; technologický předpis; zdění; monolitický strop; zařízení staveniště; strojní sestava; časový plán; kontrolní a zkušební plán; tepelný most.; Residential building; rough superstructure; construction method; masonry; část-in-place concrete floor; building site equipment; construction machinery; time schedule; quality control and test plan; thermal bridge.